Reação de clones comerciais de cajueiro ao oídio - Oliveira, Olienaide Ribeiro de (2016)
Powdery mildew has become one of the main pathogens of cashew plantations, causing damage to leaves, inflorescences, maturis, nuts and stalks. Thus, it is very important research aimed at studying the development of the disease in commercial cultivars cashew in different epidemiological stages of the disease in order to identify resistant cultivars.The objective of this study was to evaluate the reaction of commercial cultivars cashew mildew based on monitoring of severity over time disease, check the morphological difference between resistant and susceptible plant tissues and develop a natural inoculation methodology as an alternative early selection of cashew cultivars. The research was divided into three experiments at Embrapa, the first of which was in the Experimental Field of Pacajus, evaluating the reaction of eleven cultivars to mildew in three production cycles (2012, 2013 and 2014). The second was in the laboratory of electronic microscopy, studying the morphology of the powdery mildew infection process six cultivars (samples of flowers and leaves). The third test was a natural inoculation of powdery mildew method for early selection of cashew cultivars, which used ten cultivars changes with a test Fortress and other Pacajus. In the first and third tests, we evaluated the disease severity scale descriptive notes (0 to 4). In the first, it identified groups of similar cultivars in reaction to powdery mildew, through cluster analysis of three production cycles. BRS 274 cultivars BRS 275, BRS 226 and CCP 1001 were the most resistant, while the BRS 189 and cultivars CCP 06 were the most susceptible. The area under the disease progress curve (AUDPC) showed that there is difference between the cashew cultivars in reaction to powdery mildew during the crop production cycle. In the study under microscopy, it was noted in the inflorescences of cultivars a lot of upright conidiophores, except BRS 253. In the leaves, has been seen mycelium covering their surfaces with appressoria well developed, penetrating the epidermis. In sepals it found that the fungus invests in the Conidiogenesis process. In the third test, the test method was effective for cashew about the reaction of cultivars to powdery mildew on the leaves, and cultivar BRS 274 was the most resistant to powdery mildew for the two sites. In this research the cashew cultivars BRS 274, BRS 226, BRS 275 and CCP in 1001 have been identified as sources of resistance to powdery mildew and can be used in the integrated management of the disease.